The Complete Guide to ASP.NET Core MVC (.NET 5) - Patel, Bhrugen (Packt Publishing, 2021)
Learn the basic and advanced concepts of ASP.NET Core MVC (.NET 5) by building two applications and developing them on Microsoft Azure and IIS About This Video Learn new and advanced topics in ASP.NET MVC Core Build a Razor app with CRUD operations using the Entity framework for integration with the database Deploy our project website on Microsoft Azure and IIS In Detail This is a beginner to an advanced-level course on .NET 5 that will take you from basics all the way to advanced mode. This course is for anyone who is new to ASP.NET Core or who is familiar with ASP.NET and wants to take the first stab at understanding what is different in ASP.NET Core. From there, we will build multiple projects to understand all the concepts in .NET 5 as we deploy our final application on Azure as well as IIS. Throughout this course, we will understand the evolution of ASP.NET Core, and then take a look at the modified files and folder structure. We will then take a look at new concepts in ASP.NET Core. We will build a small Razor application with CRUD operations using the Entity framework for integration with the database. We will build our Bulky Book website where we will learn advanced topics in ASP.NET MVC Core. Finally, we will deploy our Bulky Book website on Microsoft Azure and IIS. By the end of the course, you will be able to build your own application using ASP.NET Core MVC, Entity Framework Core, and ASP.NET Core Identity.